A comparison of detection methods of Alaria alata mesocercariae in wild boar (Sus scrofa) meat. (December 2021) - Strokowska, Natalia; Nowicki, Marek; Klich, Daniel; Didkowska, Anna; Filip-Hutsch, Katarzyna; Wiśniewski, Jan; Bełkot, Zbigniew; Anusz, Krzysztof
Abstract: Distomum musculorum suis (DMS), the mesocercariae of Alaria alata, is typically found accidently during examination of wild boar meat for Trichinella spp. The aim of the study was to compare DMS detection methods. Briefly, 232 wild boar meat samples were tested by mesocercariae migration technique (AMT) as a reference method; of these, 104 were found to be positive. Selected positive samples were tested again with the three other methods: compressorium method (Compressor), digestion with magnetic stirrer (Digestion) and by modified digestion with Pancreatin® bile and pancreatic enzymes (D + P). The results were analyzed by logistic regression, the non-parametric Kruskal-Wallis test and the Mann-Whitney U test. Of the 43 samples found positive by the AMT, 20 were found positive by Digestion and 25 by D + P. The Compressor identified DMS in seven of the 19 tested samples. The Digestion and D + P methods gave similar intensities (P = 0.506), i.e. 1.4 and 1.3 DMS respectively, but the AMT detected seven times higher number of parasites. The probability of detection of DMS in the meat sample by the Digestion or by D + P was higher than 0.5 when at least seven (Digestion) or five (D + P) DMS were present in the sample (AMT). The Compressor was the least sensitive method: at least 14 DMS must be present in the meat sample for detection. AMT should be considered the most accurate method of DMS detection. Graphical abstract: Image 1 Highlights: AMT appears the most sensitive method to detect Alaria alata mesocercariae. AMT results are seven times higher than in digestion methods in case of intensity. Compressor method is clearly inadequate to detect Alaria alata mesocercariae.